Giada De Laurentiis's Recipe for adventure. Paris! - De Laurentiis, Giada (De Laurentiis, Giada. Giada De Laurentiis's recipe for adventure., 2013)
Siblings Alfie and Emilia are magically transported to Paris, where a case of mistaken identity finds them caught up in the behind-the-scenes drama at a traditional French cooking school.